AN INVESTIGATION OF MECHANICAL PROPERTIES ON NITRIDED AUSTENITIC STAINLESS STEEL - A Rahim, Nurkamariah (IRC, 2016)
Austenitic Stainless Steel (ASS) has been used widely in industry because of its excellent corrosion properties. However, due to its inherent austenitic structure, it exhibits slightly low hardness and wear resistance. Thus, it limits its application. In this study, the ASS are treated with gas nitriding at temperature of 400°C and 1100°C to improve the surface mechanical properties. The study aims to improve the surface hardness and scratch resistance of ASS. The effect of the nitriding treatment time and nitriding temperature to improve the surface mechanical properties are investigated. The nitriding treatment time are conducted at 4 hours, 8 hours and 12 hours. Argon gas and Nitrogen gas are used for this treatment. The microstructure and element composition profile are observed by using Optical Microscope (OM) and Scanning Electron Microscope (SEM) to investigate the formation of nitrides on the surface layer of the samples. The surface hardness of the samples is tested using Vickers Microhardness Tester.